Co(i) complexes with a tetradentate phenanthroline-based PNNP ligand as a potent new metal–ligand cooperation platform. Issue 41 (14th October 2020) - Jheng, Nai-Yuan; Ishizaka, Yusuke; Naganawa, Yuki; Sekiguchi, Akira; Nakajima, Yumiko
Abstract : A cobalt(i ) alkyl complex bearing a tetradentate phenanthroline-based PNNP ligand undergoes dearomatization of the ligand backbone skeleton upon heating and furthermore achieves H–H bond cleavage. Abstract : A series of low spin cobalt(i ) complexes bearing a tetradentate phenanthroline-based PNNP ligand (2, 9-bis((diphenylphosphanyl)methyl)-1, 10-phenanthroline), [CoCl(PNNP)] (1 ), [CoMe(PNNP)] (2 ) and [Co(CH2 SiMe3 )(PNNP)] (3 ), were synthesized and structurally identified. Complex 3 underwent a structural rearrangement of the PNNP skeleton upon heating to form [Co(PNNP′)] (4 ), which is supported by an asymmetrical PNNP′ ligand with a dearomatized phenanthroline backbone. Mechanistic studies supported that the transformation from 3 to 4 was initiated by the homolysis of either a Co–CH2 SiMe3 bond or a benzylic C–H bond. Complex 4 achieved H–H bond cleavage of H2 (1 atm) at ambient temperature, to form [Co(PNNP′′)] (6 ), in which two H atoms were incorporated into the endocyclic double bond of the PNNP′′ ligand backbone.